Lipid Granules Staining (Nile Red and Bodypy) of Different Biofuel Producing Fresh Water Microalgae Growing under Various Stress Conditions - V. Prakasam, S. Elumalai* and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Chlorella vulgaris and Diatoms were cultivated and maintained in different stress system like high light intensity (18:6, Light: Dark) and N2 limited condition.Ã‚Â After the stationary phase, the cells were stained by Nile red and Bodipy.Ã‚Â The slides were examined under fluorescence in situ hybridization microscopy, it showed the Chlorella vulgaris cultivated under N2 limited system yield high lipid bodies than light induced system and Stressed Diatoms.Ã‚Â While Bodipy is a best tool for staining algal lipid bodies than Nile Red stain. Ã‚Â